Empoweing Students’ Worksheet Of Ipa Learning On Competency Standard Classifying Animals Based On Type On Food At Sixth Grade Students In Sd Negeri 6 Sungai Putih Kecamatan Bayang - Husneti Husneti (Jurnal Ilmiah Pendidikan Scholastic, 2018)
This classroom Action Research is done in Elementary School at fourth grade No. 16 Sungai Putih kecamatan Bayang from September to December 2016. The students achievement on Natural Sciences learning at fourth grade in SD Negeri No. 16 Sungai Putih Kecamatan Bayang from several repetitions is still very low. From the two repetitions the average grade is still below the KKM that is 75. The highest score of 70 while the lowest value 50. On the second daily test is 80 and the lowest score is 50. The average of the two daily tests is 67. The purpose of this study is to improve the learning outcomes of animals based on the type of food in Natural Science learning for the fourth grade students of SD Negeri No. 16 Sungai Putih Kecamatan Bayang through the empowerment of students’ worksheets. The setting of the research is in public primary schools No. 16 Sungai Putih Kecamatan Bayang. This research was held on September to December 2016. This research is Classroom Action Research (Classroom Action Research). The action consists of two actions in two cycles. Each cycle consists of four stages namely Planning, acting, observing, and reflecting. The class studied is the fourth grade students of SD Negeri No. 16 Sungai Putih Kecamatan Bayang with the number of students 29 people. After the first cycle is executed the teacher implementing the practice of direct learning obtained results. In cycle 1 the average grade value increased to 75. In cycle 2 the average value was 86. So from the initial to the final condition there was an increase in learning outcome from the mean of 67 to 86. From the results of the action research conducted in two cycles, obtained significant improvement, so that it can be concluded that by empowering the Student Worksheet to improve learning outcomes in category animals based on the type of food for fourth grade students of SD Negeri No. 16 Sungai Putih Kecamatan Bayang. For that teachers are expected to always provide guidance to students to remain diligent learning, through reading, discussing to always practice working on student worksheets, so it can achieve the desired goals.